The Successful Removal of a Foreign Body in the Spleen via Diaphragm Laceration Site by Video-Assisted Thoracoscopic Surgery - Yang Bin Jeon; Sung Youl Hyun; Dae Sung Ma (Journal of Trauma and Injury)
A 73-year-old man, who, in an inebriated state, had slipped in a flowerbed and was wounded on the left flank, was transferred to Trauma Center, Gil Medical Center, Gachon University College of Medicine. Based on the chest and abdominopelvic computed tomography, he was diagnosed with multiple rib fractures and hemopneumothorax on the left hemithorax and was found to have a bony fragment in the spleen. He had not presented peritonitis and exsanguinous symptoms during the observation period. Seven days later, computed tomography of the abdomen showed suspected diaphragmatic injury and a retained foreign body in the spleen. On exploration by video assisted thoracoc surgery (VATS), a herniated omentum through the lacerated site of the diaphragm was observed. After omentectomy using Endo Gia, the foreign body in the spleen was observed through the lacerated site of the diaphragm. Traumatic diaphragm rupture with a foreign body, in the spleen, was successfully managed by video assisted thoracic surgery via the lacerated site of the diaphragm.